2003
DOI: 10.1007/bf02976863
|View full text |Cite
|
Sign up to set email alerts
|

Anti-complementary activity of protostane-type triterpenes fromAlismatis rhizoma

Abstract: Four protostane-type triterpenes, alisol B 23-acetate (1a), alisol C 23-acetate (2a), alisol B (3a), and alisol A 24-acetate (4a), were isolated from the rhizome of Alismatis plantago-aquatice L. var. orientale Samuelson (Alismataceae) and eleven protostane derivatives (compounds 1-11) were obtained by selective modification from alisol B 23-acetate (1a). These compounds were investigated for their anti-complement activity against the classical pathway of the complement system. Alisol B (3a) and alisol A 24-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…The best described anti-complementary agents are polysaccharides, flavones and triterpenes [27][28][29]. But most of the targets of these agents in the complement activation cascade were not fully elucidated due to lack of the efficient method to purify the active ingredients to homogeneity from crude extract and the expensive of the complementdeficient serum.…”
Section: Discussionmentioning
confidence: 99%
“…The best described anti-complementary agents are polysaccharides, flavones and triterpenes [27][28][29]. But most of the targets of these agents in the complement activation cascade were not fully elucidated due to lack of the efficient method to purify the active ingredients to homogeneity from crude extract and the expensive of the complementdeficient serum.…”
Section: Discussionmentioning
confidence: 99%
“…The best described anticomplementary agents are polysaccharides, flavones and triterpenes [43][44][45]. But most of the targets of these agents in the complement activation cascade were not fully elucidated due to lack of the efficient method to purify the active ingredients to homogeneity from crude extract and the expensive of the complement deficient serum [39].…”
Section: Discussionmentioning
confidence: 99%
“…Alisol B acetate is a major ingredient isolated from Alismatis rhizoma and has been used for urological diseases in traditional Chinese medicine. In recent years, the pharmacological characterization of alisol B acetate has been identified and several biological activities have been defined, such as the inhibitory effects on lipopolysaccharide [3] , the inhibition of complementary activity [4,5] and antibodymediated allergic reaction [6] . Furthermore, it has been demonstrated that alisol B acetate induces cell death in hepatoma and leukemia cells [7,8] .…”
Section: Introductionmentioning
confidence: 99%